Enhancing Regional Economic Development through Digital Readiness Analysis and a Transformation Model for Creative MSMEs in Padangsidimpuan City - Siregar, Muhammad Rifai; Juliana, Juliana; Fadila, Fadila (JURNAL MANAJEMEN MOTIVASI, 2025)
This study explores how digital readiness shapes the transformation of creative MSMEs in Padangsidimpuan City and its role in strengthening the regional economy. The findings highlight challenges in digital infrastructure and human resource capacity. From these insights, a digital transformation model was proposed, built on three pillars: strengthening digital infrastructure, enhancing HR capacity, and fostering penta-helix collaboration. The study contributes to the literature on MSME digital transformation and provides practical insights for advancing digitalization in semi-urban contexts.